2022
DOI: 10.1097/sap.0000000000003155
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Trends in Patients Requiring Sternectomy and Reconstruction

Abstract: Introduction: Comorbidity trends after median sternectomy were studied at our institution by Vasconze et al (Comorbidity trends in patients requiring sternectomy and reconstruction. Ann Plast Surg. 2005;54:5). Although techniques for sternal reconstruction have remained unchanged, the patient population has become more complex in recent years. This study offers insight into changing trends in this patient population. Methods: A retrospective review was performed of patients who underwent median sternectomy fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Eleven studies on thoracic surgery were identified 33 , 35 , 37 , 39 , 41 , 43 , 45 , 47 , 49 , 51 , 53 , including seven sternal wound reconstructions and four breast reconstructions. A total of 1005 people were included, 286 of whom received omentoplasty and 719 of whom did not.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies on thoracic surgery were identified 33 , 35 , 37 , 39 , 41 , 43 , 45 , 47 , 49 , 51 , 53 , including seven sternal wound reconstructions and four breast reconstructions. A total of 1005 people were included, 286 of whom received omentoplasty and 719 of whom did not.…”
Section: Resultsmentioning
confidence: 99%